Regional axonal loss in the corpus callosum correlates with cerebral white matter lesion volume and distribution in multiple sclerosis. - Evangelou, N; Konz, D; Esiri, M; Smith, S; Palace, J; Matthews, P (2000)
Previous imaging studies have suggested that there is substantial axonal loss in the normal-appearing white matter (NAWM) of brains from multiple sclerosis patients and that this axonal loss may be an important determinant of disability. Recently, substantial axonal loss in the NAWM has been confirmed directly in post-mortem tissue. Whether the NAWM changes occur as a consequence of damage to axons traversing lesions or to a more diffuse injury process is uncertain. Using formalin-fixed brains of eight multiple sclerosis patients and eight age-matched controls, we examined the relationship between demyelinating lesion load in three volumes of the cerebral white matter and the loss of axons in NAWM of the corresponding three projection regions (anterior, middle, posterior) in the corpus callosum (CC). There was a significant loss of calculated total number of axons crossing the CC in each of the three regions relative to the non-multiple sclerosis controls. Strong correlations were found between the regional lesion load and both the axonal density (r = -0.673, P: = 0.001) and the total estimated number of axons crossing the corresponding projection area in the CC (r = -0. 656, P: = 0.001) for the patients. This suggests that Wallerian degeneration of axons transected in the demyelinating lesions makes a major contribution to the substantial, diffuse loss of axons in the NAWM in multiple sclerosis. These findings emphasize the need to consider the consequences of multiple sclerosis lesions in terms of both local and distant effects in functionally connected regions of the brain.